REIMAGINING MANAGEMENT EDUCATION IN INDIA: WITH REFERENCE TO NATIONAL EDUCATION POLICY-2020 - Jadav, Jayendrasinh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The landscape of management education in India is undergoing a transformative shift, catalysed by the introduction of the National Education Policy (NEP) 2020. This research paper explores the implications of the NEP 2020 on the structure, curriculum, and pedagogy of management education in India. The NEP envisions a holistic, multidisciplinary, and skill-oriented approach to education, emphasizing the need for a comprehensive overhaul of existing educational frameworks to align with global trends and societal needs. By analysing key aspects of the policy, such as the promotion of critical thinking, innovation, and the integration of technology, this paper highlights the opportunities and challenges that lie ahead for management institutes in India. The paper also delves into the need for a shift from traditional teaching methodologies to more dynamic, experiential learning environments that nurture entrepreneurial spirit, leadership skills, and ethical decision-making. Through a detailed analysis, this research aims to provide actionable insights into how management education can be reimagined in India to meet the demands of the 21st century.